CHANGES IN LABOUR PRODUCTIVITY IN THE AGRIBUSINESS IN EUROPEAN UNION COUNTRIES - Mrówczyńska-Kamińska, Aldona; Baer-Nawrocka, Agnieszka (Acta Scientiarum Polonorum. Oeconomia, 2018)
The main aim of the paper is to identify the changes in labour productivity in the agribusiness and to define its relationship to labour productivity in the entire national economy of the EU countries. Labour productivity is expressed as gross value added per employee in agribusiness as a whole and its three zones (I – industries manufacturing means of production and services for agriculture and the food industry, II – agriculture, III – food industry). The analysis concerns selected years from 1995 to 2010, which are the most recent available data. The gross value added in agribusiness were calculated by means of the formula suggested by Woś in 1979. As it results from the analyses, despite favorable changes, the productivity of labour in the agribusiness in the new EU Member States remains at a lower level than in most of the EU-15 countries. The main reason behind the differences in the levels of agribusiness labour productivity is a surplus of the labor force in the agriculture in the most EU-12 countries. Moreover, the EU-15 countries especially from Western and Northern Europe demonstrate smaller differences between the labour productivity in agribusiness and other sectors of the national economy.